2014
DOI: 10.1001/jamainternmed.2014.3404
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Use of Ezetimibe After the ENHANCE Trial, 2007 Through 2010

Abstract: IMPORTANCE Results from the Ezetimibe and Simvastatin in Hypercholesterolemia Enhances Atherosclerosis Regression (ENHANCE) trial, announced in January 2008, demonstrated that ezetimibe use lowered cholesterol levels but did not slow the progression of atherosclerosis.OBJECTIVE To examine the association of this announcement with national patterns of ezetimibe prescribing, including medication initiation and discontinuation, as well as predictors of use. DESIGN, SETTING, AND PARTICIPANTSRetrospective analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…The trends in the use and costs of ezetimibe are similar to those reported for the United States, Canada, and Europe. 7,13,17 In contrast to some other studies, 18,19 we did not see any obvious reduction in ezetimibe use after the ENHANCE trial was published in 2008. 8 That trial showed that ezetimibe plus simvastatin, compared to simvastatin alone, had no effect on intima-media thickness in atherosclerosis in patients with familial hypercholesterolemia.…”
Section: Underreporting Rates For Voluntary Ae Reports Have Been Esticontrasting
confidence: 99%
“…The trends in the use and costs of ezetimibe are similar to those reported for the United States, Canada, and Europe. 7,13,17 In contrast to some other studies, 18,19 we did not see any obvious reduction in ezetimibe use after the ENHANCE trial was published in 2008. 8 That trial showed that ezetimibe plus simvastatin, compared to simvastatin alone, had no effect on intima-media thickness in atherosclerosis in patients with familial hypercholesterolemia.…”
Section: Underreporting Rates For Voluntary Ae Reports Have Been Esticontrasting
confidence: 99%
“…Later analysis showed that ezetimibe use was indeed related to variability in formulary restrictiveness [172]. Through 2007-2010, 29.1 % of continuously eligible adults obtained at least one lipid-lowering medication [173]. Among them, 17.8 % were given ezetimibe and 95.3 % another agent, usually statins.…”
Section: Ezetimibementioning
confidence: 99%
“…Critics rightly started questioning the validity of using ezetimibe based on its ability to lower LDL‐C. Previous sales of ezetimibe which had been high based on its lipid‐lowering efficacy and convenience then fell . Later the results of the torcetrapib outcomes trial again with a drug efficacious at lowering LDL‐C were also adverse but followed negative cIMT surrogate outcomes trials .…”
Section: Comparative Effects Of Fibrates Niacin and Ezetimibe On Cormentioning
confidence: 99%